Визначення оптимальної кількості полюсів статора TFM в генераторному режимі роботи - Єгоров, Андрій Володимирович; Маслєнніков, Андрій Михайлович; Дунєв, Олексій Олександрович; Ляйдхольд, Роберто; Штаманн, Маріо (Одеський національний політехнічний університет, 2017)
Представлена 3D модель TFM генератора і результати чисельно-польового розрахунку в програмі Ansys Maxwell, на базі яких створена методика розрахунку, яка дозволяє визначити оптимальну кількість витків котушки та полюсів на статорі. Отримано рівняння залежності індуктивності котушки й магнітної індукції в осерді статора від кількості полюсів статора, завдяки яким є змога провести аналітичний розрахунок.

The TFM model of generator was designed and calculated using numerical-field method in the program Ansys Maxwell. The results of these calculations was given in this article and analyzed, which allowed to find the optimum number of the coil turns and the optimum number of the stator poles with the highest machine efficiency and useful output power. Purpose. Plot an external characteristic of the TFM generator for a different number of turns and find the most optimal configuration of the stator core with the most effective number of poles. Methodology. Modeling of electro-magnetic processes in TFM with generator mode and analytical comparison of these results with experimental data. Results. The equation of dependence of the coil inductance and magnetic induction in the stator core on the number of stator poles is obtained. Also due to this dependence we got the possible to perform the future analytical calculations. Originality. TFM - is a specific synchronous electrical machine with a non-classic constructive design, but due to their work features, reliability, simplicity of control and manufacture, they have been receiving a wide interest in a modern research works. Practical value. A 3D model design of the TFM with the disk type of rotor was presented, and the results of its experimental research was shown, which help to revealed the dependence of the number of stator poles on the generated EMF in generator mode. A common equation of EMF was also obtained, which allows to predict the EMF values in the stator coil of TFM generator with a different numbers of turns and poles, which will allow to design the TFM machines with a high accuracy in the future.
Finding the optimal number of TFM stator poles in generator mode
Keywords: електричні машини; моделювання; індуктивність котушки; насичення; магнітна індукція; generator; simulation; coil inductance; saturation; magnetic induction; pole